Casos policiales. Una genealogía del enigma en la Argentina - Calabrese, Elisa (Anales de Literatura Hispanoamericana, 2008)
This work proposes a genealogical approach to detective literature to show the show the uses of the genre. In this way, starting out with Jorge Luis Borges’s «Death and the Compass», birth of Argentine detective writing, we can observe how parody diverts the genre by means of inversion, displacement and political reference, which refers us to the production context. Next, we will consider how this displaced use of the genre, which generates a tradition in the Argentinean culture, can be observed in the novel of Guillermo Martínez, Imperceptible Crimes, of 2003, which can be read as a rewriting Jorge Luis Borge´s «The Garden of Forking Paths.»